Pendidikan Kesehatan tentang Reproduksi pada Remaja di RT 15 Kelurahan Thehok - Hesty Hesty (3031-8572, 2022)
Adolescence is a transitional period between childhood and adulthood. In this phase, physical changes tend to be more dominant, such as sexual function, which is one of the characteristics of the development of adolescence or is called puberty. Physical changes that begin to mark reproductive maturity occur in adolescents with rapid physical growth, including the growth of the reproductive organs to reach maturity, so that they are able to carry out the reproductive function. The dedication method that will be applied is lectures, discussions. The implementation of this community service activity was carried out in July 2021 at RT 15 Thehok Village, Jambi City. This activity aims to provide education to adolescents to understand reproduction in adolescence so that it is more efficient. The target of education in this activity is 15 teenagers. The implementation of reproductive education for adolescents is going well. This community service activity provides positive benefits to the community, especially to teenagers. This activity can assist health workers in suppressing reproductive health problems in adolescents, assisting parents in understanding their children, especially dealing with adolescence to provide knowledge and monitor children about maintaining reproductive health and avoiding reproductive health problems, assisting teachers in preventing reproductive health problems and assisting the nation and state in producing youth who will become reliable human resources. Participants were very enthusiastic in participating in counseling, there was an increase in understanding of 98% in adolescents about reproductive health, how to maintain and care for reproductive health.